INTERNAL CONTROL SYSTEMS EFFECTIVENESS AND THE PREVALENCE OF ACCOUNTING FRAUD - Salsabila, Ismi; Mutmainah, Ina (E-Jurnal Akuntansi TSM, 2026)
Fraud is defined as the fraudulent manipulation and pursuit of profits for parties who report the assets and financial accounts of a corporation. Fraud can happen in a variety of industries, including the public and commercial sectors. This study aims to identify the partial and simultaneous effects of information asymmetry, religiosity, appropriateness of compensation, and the efficiency of the internal control system on the likelihood of accounting fraud in the Pemalang Regency government sector. Quantitative research is the research technique used. Purposive sampling is the method of selection used in this investigation. 100 employees, particularly those in the finance department, of the SKPD (local and regional government institutions) of Pemalang Regency served as the study's sample population. The study's data analysis methods included multiple linear regression analysis. Unless the variables of compensation suitability have no effect on the propensity of accounting fraud, the variables of knowledge asymmetry, religiosity, and the efficacy of the internal control system partially affect the tendency to accounting fraud. Information asymmetry, religiosity, appropriateness of reward, and the efficiency of the internal control system all work together to influence the likelihood of accounting fraud in Pemalang Regency's public sector.